The Bolshevist staff of "Rabočij", with, in the middle of the second row, f.l.t.r.: Trockij, Skrypnik, Derbyshev, Riazanov. From: ACCR/1359
The Bolshevist staff of "Rabočij", with, in the middle of the second row, f.l.t.r.: Trockij, Skrypnik, Derbyshev, Riazanov. From: ACCR/1359.